2011
DOI: 10.3324/haematol.2011.045757
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic stem cell transplantation after reduced intensity conditioning in patients with relapsed or refractory Hodgkin's lymphoma. Results of the HDR-ALLO study - a prospective clinical trial by the Grupo Espanol de Linfomas/Trasplante de Medula Osea (GEL/TAMO) and the Lymphoma Working Party of the European Group for Blood and Marrow Transplantation

Abstract: BackgroundAlthough Hodgkin's lymphoma is a highly curable disease with modern chemotherapy protocols, some patients are primary refractory or relapse after first-line chemotherapy or even after high-dose therapy and autologous stem cell transplantation. We investigated the potential role of allogeneic stem cell transplantation in this setting. Design and MethodsIn this phase II study 92 patients with relapsed Hodgkin's lymphoma and an HLA-identical sibling, a matched unrelated donor or a one antigen mismatched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(152 citation statements)
references
References 34 publications
11
135
1
4
Order By: Relevance
“…40,41 Importantly, several studies have shown that chemosensitivity at transplantation remains a major predictor of outcome of RIC allogeneic SCT (RIC-allo). 38,41,42 The expert panel acknowledges that RIC-allo may have a role in HL. For patients with primary refractory disease, and for those relapsing after first-line standard-dose chemotherapy, RIC-allo without previous ASCT is not recommended.…”
Section: Allogeneic Stem-cell Transplantationmentioning
confidence: 99%
“…40,41 Importantly, several studies have shown that chemosensitivity at transplantation remains a major predictor of outcome of RIC allogeneic SCT (RIC-allo). 38,41,42 The expert panel acknowledges that RIC-allo may have a role in HL. For patients with primary refractory disease, and for those relapsing after first-line standard-dose chemotherapy, RIC-allo without previous ASCT is not recommended.…”
Section: Allogeneic Stem-cell Transplantationmentioning
confidence: 99%
“…Unfortunately, approximately 50% 6 of these patients will relapse again, and at this point treatment options become limited to palliative chemotherapy, radiotherapy or experimental approaches, including new molecules and, in selected cases, allogeneic stem cell transplant (allotransplant). 7,8 Brentuximab vedotin (BV, previously known as SGN-35, Seattle Genetics, WA, USA) is a novel antibody-drug conjugate targeting CD30 linked to a payload comprising a potent tubulin toxin, monomethyl auristatin E. The cell surface antigen CD30 is ubiquitous across Hodgkin Reed-Sternberg 9 and ALCL 10 cells. Two pivotal studies have demonstrated its efficacy in relapsed/refractory Hodgkin lymphoma (HL) 11 and anaplastic large cell lymphoma (ALCL), 12 with overall response rates (ORR) of 75% and 86%, respectively, when administered as monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…At our Institution, tandem HDC or tandem auto-allo-SCT are preferred therapeutic options in lymphoma patients not reaching CR after salvage chemotherapy, based on the poor outcome reported with the use of single HDC; [18][19][20] indeed, disease status before transplantation is a well-known, independent prognostic factor in lymphoma patients. 18,[21][22][23] From present results it emerges that HD-PAM as a bridge therapy may be a challenging option in this setting of poor-prognosis patients. Interestingly, in our hands HD-PAM converted 77% of refractory patients (17 out of 22 patient in SD or PD before HD-PAM) into PR, or even CR (Figure 1), thus enabling them to proceed to further therapy.…”
Section: Discussionmentioning
confidence: 84%